Práticas discursivas em blogs políticos: uma observação sobre a participação política e as trasnformações que acompanham o espaço público - Bevilaqua, Anna Karinna Dantas (2012)
This work discuss about the transformation of public space, based on the recent challenges imposed by communication practices that are renewed and recopying of the sociocultural contexts of everyday life. The study presents theoretical and empirical reports of regional political blogs. In this issue, it looks for understand the political participation in the Internet space, examining the reconfigurations that accompany social relations and new forms of interaction that are merged in the media scene. The ambience of the study limits comments of readers in two political blogs in Rio Grande do Norte, Território Livre, and Thaisa Galvão. The observation concerns about the democratic participation of citizens in matters of collective interest, during the 2010 election. The analysis update the debate on democratic discussion and conversation everyday, trying to grasp changes in social practices in virtual platforms. From this perspective, the work restores some conceptual notions that involve the public places, identifying the changes that appear in the virtual and traditional spheres, with the emergence of new places of conversations, from the Internet usage. Are also compared to similarities and differences between the two elements of the analysis. It is possible, therefore, the communication process of the two discursive spaces with ideas from the public sphere, trying to analyze the duality between public, private, and political participation in these virtual places